In Search of a Different History: The Remains of Burlesque in Montreal - Mansbridge, Joanna (Canadian Theatre Review, 2014)
: Taking Elin Diamond’s and Rebecca Schneider’s recent work in drama and performance studies as a starting point, this essay looks at two eras of burlesque in Montreal—the 1940s-50s and 2012—tracing a shifting landscape of popular entertainment, politics, religion, and social attitudes toward female sexuality. There is a central question underlying this examination: Why burlesque? Why now (or, rather, again?). I argue that burlesque offers an archive that evokes a different, more glamorous history than the one passed down to women by second-wave feminism. Burlesque also provides an alternative to popular culture’s commodification of female sexuality, technology’s mediation of social life, and heteronormative culture’s privatization of sexuality, giving women—and men—a stage on which to make fun of our cultural fixation with sex and the female body. Both nostalgically looking back and eagerly reaching for the new, neo-burlesque repeats the past as it simultaneously reinvents it.
Publisher: University of Toronto Press

Interpreting Brazilianness: Reception and Representation in the Brazilian Music Scenes of Toronto and Montreal - Mercier, Catherine G. (Université de Toronto, 2014)
In Toronto and Montreal, Brazilian popular music performances constitute a context for intercultural encounter. Performances offer Brazilians the opportunity to present their culture of origin while emphasising their identification with it. The issue of representation is quite complex, however, due to the involvement of a majority of non-Brazilian musicians, audience members, artistic directors, producers, promoters, and journalists. This dissertation focuses on music reception and cultural representation and how these may influence each other after music has been decontextualised and recontextualised. I look closely at local non-Brazilian audiences possessing different degrees of familiarity with Brazilian music, and I demonstrate how cultural stereotypes influence their conceptions and expectations of Brazilian music, culture, and people. I argue that a desire for cultural difference and the exotic, encouraged by discourses of cultural diversity, influences the reception of performances. I suggest that, through the privileged gaze of non-Brazilian attendees, performances may be adjusted to correspond to audience fantasies of Brazil. Some non-Brazilians would like to become knowledgeable of, and even intimate with Brazilian culture, which would satisfy their desire to be cosmopolitan. However, pleasure frequently matters more to them than a nuanced understanding of Brazilian culture; this explains, I contend, why some Torontonians and Montrealers have become comfortable with essentialist and stereotypical representations. I examine how some non-Brazilian musicians, promoters, and band agents reinforce mythologies of Brazil to meet audience demands and sometimes to satisfy their own fantasies. I analyse the reproduction of similarly problematic discourses on Brazil in the presentations of Brazilian artists as both a form of autoexoticism and a particular type of tactical or strategic essentialism. Rather than to represent and understand Brazilian culture, I argue that, through local music performances, Brazilians and non-Brazilians in Toronto and Montreal interpret Brazilianness.